Investigating El Niño-Southern Oscillation and society relationships - Zebiak, Stephen E.; Orlove B; Vaughan, Catherine; Muñoz, A.G.; Hansen, James; Troy T; Thomson, M.; Lustig, A.; Garvin S (Wiley, 2015)
Throughout at least the past several centuries, El Niño-Southern Oscillation (ENSO) has played a significant role in human response to climate. Over time, increased attention on ENSO has led to a better understanding of both the physical mechanisms, and the environmental and societal consequences of the phenomenon. The prospects for seasonal climate forecasting emerged from ENSO studies, and were first pursued in ENSO studies. In this paper, we review ENSO's impact on society, specifically with regard to agriculture, water, and health; we also explore the extent to which ENSO-related forecasts are used to inform decision making in these sectors. We find that there are significant differences in the uptake of forecasts across sectors, with the highest use in agriculture, intermediate use in water resources management, and the lowest in health. Forecast use is low in areas where ENSO linkages to climate are weak, but the strength of this linkage alone does not guarantee use. Moreover, the differential use of ENSO forecasts by sector shows the critical role of institutions that work at the boundary between science and society. In a long-term iterative process requiring continual maintenance, these organizations serve to enhance the salience, credibility, and legitimacy of forecasts and related climate services.